Political Press. Manuel Gonzalez Prada, El Germinal and the Union Nacional (1899-1902) - Rosario, Emilio (2010)
This is research study the life the «Unión Nacional» saw thanks your newspaper «El Germinal», which was published during there years, time in that Gonzalez Prada wrote articles and was the boss. However Prada was alone also fought with yours politics friends. The conflict inside finished with out of Prada in this organization